Efek Adanya Reward dan Motivasi Kerja terhadap Kinerja Karyawan melalui Kesejahteraan Karyawan pada PT. PLN (Persero) Kabupaten Sijunjung - Amanda Sal Sabila; Marta Widian Sari; Nila Pratiwi (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This1research1aims1to1find1out1how1much1influence rewards and work motivation have on employee1performance1through1employee welfare at PT. PLN (PERSERO) Sijunjung district. The data analysis method uses a questionnaire, with a sample of 30 respondents1using1a1saturated sample method or census method. The method used1is a1quantitative1method with structural equation modeling (SEM) with Partial Least Square 3.0. By distributing a questionnaire to 421respondents. The results of data analysis concluded that Rewards had no significant effect on employee welfare variables with a significant level (0.186 < 0.07). Work motivation variables had1a significant effect on employee welfare with a significant level (0.000 > 0.07). The1reward variable has a significant effect on employee performance with a significant level (0.017 < 0.07). The work1motivation1variable does not have a significant effect on employee1performance at a significant1level (0.830 < 0.07). The employee welfare variable has a significant influence on1employee1performance with a significant level (0.014 < 0.07). The work motivation variable has a1significant effect on employee1welfare1through employee performance with a significant level (0.027 < 0.07), in other words there is a significant influence of work motivation on employee welfare1through employee1performance. And1the reward variable does not have a significant effect on employee welfare through employee performance with a significant level (0.295 > 0.07). In the sense that there is no significant1influence1of1reward on employee welfare through employee performance.